IMPLEMENTING FRAMEWORK OF CEFR FOR TEACHING ENGLISH LANGUAGE IN NON-ENGLISH STUDY PROGRAM - Rifiyanti, Hafizah (Faculty of Teacher Training and Education, English Department, UNISKA, Kediri, 2023)
The assumption that English lessons are difficult makes some students feel reluctant to improve their English skills. This learning difficulty has an impact on the decline in academic achievement of students who are running this education. For this reason, the author felt the need to conduct a study on how effective the CEFR with an action-oriented approach is used in teaching English. This research was conducted by determining the students' actual level of English proficiency, setting achievable learning goals, and assisting students in more purposeful learning. The CEFR is a frame of reference used to measure a person's language ability, including English. This study is quantitative research. To measure the effectiveness of the study, pre and post-test assessments were used. The value of the pre and post-test assessment is the research data. The instrument used to collect data was the assessment of the English for Communication course. The respondents of this study were 63 students of Informatics Engineering and Information Systems 1st semester, Institut Bisnis dan Informatika 1957. The average score of students before and after the provision of CEFR material is different or there is an effect of increasing student scores from 55 to 72. It is very important to adjust the CEFR to the context and needs of students because the CEFR is a framework and not a curriculum. The findings of this study imply the following, namely recognizing the proficiency level of the learners: This study can reveal the proficiency level of English learners which can help align the curriculum with the CEFR levels. Determining areas of strength and weakness. Furthermore, this information can help design courses and select materials and activities that suit the needs of students and their proficiency levels. Lecturers can create instruments for assessment and evaluation using the CEFR framework.